Empowering tuberculosis genomic surveillance in Limpopo, South Africa through capacity building - Makondo, Vukosi Treasure; Kaapu, Kabelo Gabriel; Wells, Felicia; Sharma, Abhinav; Lekalakala-Mokaba, Molebogeng Ruth; Warren, Robin; Conceição, Emilyn Costa; Rukasha, Ivy (Frontiers in Public Health, 2025)
IntroductionLimpopo, a predominantly rural province in South Africa, faces significant challenges in the management of tuberculosis (TB) due to its high mobility and limited healthcare infrastructure. This study aims to improve the genomic surveillance of TB in Limpopo through capacity building initiatives.MethodsA comprehensive training program was implemented that focuses on both theoretical and practical aspects of TB research, including whole genome sequencing (WGS) and bioinformatics. Sputum samples from 232 patients diagnosed with pulmonary TB were collected, with 30 isolates selected for WGS analysis. The MAGMA bioinformatics pipeline was used for genomic analysis, identifying drug resistance mutations and phylogenetic relationships.ResultsOf the 28 Mycobacterium tuberculosis (Mtb) isolates analyzed, 53.6% were females, with a median age of 39 years. The isolates predominantly belonged to Lineage 4 (53.6%) and Lineage 2 (35.7%). High levels of drug resistance were observed, with 100% of isolates resistant to rifampicin and 61% resistant to isoniazid. In particular, 54% of the isolates were resistant to fluoroquinolones (FLQs) and 18% showed resistance to bedaquiline (BDQ). Phylogenetic analysis revealed two distinct clusters, indicating localized and interdistrict transmission.ConclusionThe study highlights the genetic diversity and drug resistance patterns of Mtb in Limpopo, highlighting the need for continued genomic surveillance and tailored public health interventions. Capacity building efforts have laid the groundwork for improved TB diagnosis and surveillance in this strategic region.